Possible Underlying Mechanism for Hydrogen Peroxide-Induced Electromechanical Suppression in Human Atrial Myocardium - Shih-Hurng Loh; Jong-Shiaw Jin; Chien-Sung Tsai; Chao-Ming Chao; Yin Tsai; Wei-Hwa Chen; Tzu-Hurng Cheng; Chao-Chin Chuang; Cheng-I Lin (Elsevier, 2003)
Hydrogen peroxide (H2O2) and its metabolites have been shown to exert complex effects on the cardiac muscle during cardiac ischemia/reperfusion. The aim of the present study, by perfusing H2O2 or/and different scavengers of oxygen free radicals (OFRs) into the human atrium, is to characterize the electropharmacological effects of H2O2 and explore its possible underlying mechanism. Atrial tissues obtained from the heart of 19 patients undergoing corrective cardiac surgery were used. Transmembrane action potentials were recorded using the conventional microelectrode technique, and contraction of atrial fibers was evaluated in normal [K]o (4 mM) in the absence and presence of tested agents. H2O2 (30 μM-3 mM) had a biphasic effect on the contractile force (an increase, followed by a decrease), reduced the 0-phase depolarizing slope (dV/dt), and prolonged the action potential duration (APD) in a concentration-dependent manner. However, even at a concentration as high as 3 mM, H2O2 did not influence diastolic membrane potential (DMP). Pretreatment with N-(mercaptopropionyl)-glycine (N-MPG), a specific scavenger of the · OH free radical, significantly blocked the 3 mM H2O2-induced electromechanical changes, while the pretreatment with L-methionine (L-M), a specific scavenger of HOCl free radical, did not. Our data suggests that the toxic effects of H2O2 are caused mainly through the generation of · OH, which is attributed to the electropharmacological inhibitory effects seen in the human atrium.